Cognitive Behavioral Therapy and Clinical Applications - Şenormancı, Ömer; Şenormancı, Güliz (IntechOpen, 2018)
The main purpose of this book is to be useful in daily practice to clinicians, including less-discussed subjects that are frequently encountered in practice. For this, it was aimed to explain the formulation of the disorder in light of the basic CBT model in each chapter and then to present the treatment approach of the disorder with case examples. We believe that the case examples, which came from the authors' own practices, are the strength of the book.